2022
DOI: 10.3389/fnagi.2022.854026
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for Osteoarthritis: A Literature Review of Pathology and Mechanism

Abstract: Osteoarthritis (OA) has a very high incidence worldwide and has become a very common joint disease in the elderly. Currently, the treatment methods for OA include surgery, drug therapy, and exercise therapy. In recent years, the treatment of certain diseases by exercise has received increasing research and attention. Proper exercise can improve the physiological function of various organs of the body. At present, the treatment of OA is usually symptomatic. Limited methods are available for the treatment of OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 225 publications
0
20
0
1
Order By: Relevance
“…In addition, it has been found that older adults suffer from chronic diseases of hyperglycemia, and a fixed number of walks per day for many years can effectively control blood glucose [ 72 ]. Some people may question whether frequent walking among older adults will affect the joints, but studies have shown that walking in older adults has a positive lubricating and protective effect on bone joints [ 73 , 74 , 75 ]. Since walking has the effect of promoting health in older adults, how many steps should older adults walk every day?…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that older adults suffer from chronic diseases of hyperglycemia, and a fixed number of walks per day for many years can effectively control blood glucose [ 72 ]. Some people may question whether frequent walking among older adults will affect the joints, but studies have shown that walking in older adults has a positive lubricating and protective effect on bone joints [ 73 , 74 , 75 ]. Since walking has the effect of promoting health in older adults, how many steps should older adults walk every day?…”
Section: Discussionmentioning
confidence: 99%
“…Under normal healthy conditions, the streaming potential is apparently able to stimulate the biogenesis of cartilage and counter the degradation by wear and tear in a continuous cycle. One of the current recommendations for people at risk of developing OA is exercise ( Roos and Dahlberg, 2005 ; Racunica et al, 2007 ; Ravalli et al, 2019 ; Kong et al, 2022 ). Exercise may exert this effect by enhancing the magnitude of streaming potentials thereby stimulating chondrocytes to produce new ECM.…”
Section: Cartilage In a See/saw Mode A Cliffhanger Towards Osteoarthr...mentioning
confidence: 99%
“…The cartilage can therefore buffer the mechanical stress between the tibia and femur during exercise and decrease friction [1]. Aging and aberrant mechanical load-caused anterior cruciate ligament (ACL) rupture will lead to the cell loss of chondrocytes and extracellular matrix (ECM) degradation in articular cartilage and further cause osteoarthritis (OA) [2,3]. Once OA occurs, inflammatory factors are highly expressed and pervasive in the synovial fluid, and then the matrix metalloproteinases 2 of 18 (MMPs) is activated, further adding to the degradation of ECM [4,5].…”
Section: Introductionmentioning
confidence: 99%